2015
DOI: 10.1186/s40001-015-0091-y
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic epidural anesthesia improves outcomes in patients undergoing cardiac surgery: meta-analysis of randomized controlled trials

Abstract: To assess the efficacy of thoracic epidural anesthesia (TEA) with or without general anesthesia (GA) versus GA in patients who underwent cardiac surgery, PubMed, Embase, the Cochrane online database, and Web of Science were searched with the limit of randomized controlled trials (RCTs) relevant to ‘thoracic epidural anesthesia’ and ‘cardiac surgery’. Studies were identified and data were extracted by two reviewers independently. The quality of included studies was also assessed according to the Cochrane handbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 53 publications
(30 reference statements)
2
28
0
2
Order By: Relevance
“…[100][101][102] Thoracic Epidural Anesthesia Thoracic epidural anesthesia is associated with a lower incidence of cardiopulmonary complications and provides excellent postoperative pain control 75,[103][104][105] Despite studies showing decreased pain scores and opioid consumption in the acute postoperative period, no reduction in chronic pain incidence or severity has been shown. 106,107 Intrathecal Opioids Intrathecal opioids are often used in fast-track cardiac anesthesia to improve acute postoperative pain scores.…”
Section: Transdermal Lidocainementioning
confidence: 99%
“…[100][101][102] Thoracic Epidural Anesthesia Thoracic epidural anesthesia is associated with a lower incidence of cardiopulmonary complications and provides excellent postoperative pain control 75,[103][104][105] Despite studies showing decreased pain scores and opioid consumption in the acute postoperative period, no reduction in chronic pain incidence or severity has been shown. 106,107 Intrathecal Opioids Intrathecal opioids are often used in fast-track cardiac anesthesia to improve acute postoperative pain scores.…”
Section: Transdermal Lidocainementioning
confidence: 99%
“…Here we present four topics with more than one meta-analysis (Table 2 ). One of them – “the effect of perioperative epidural analgesia combined with general anesthesia on mortality in cardiac surgery” – did not pass the proof-of-concept test: P -value was >0.05 in any of the 3 included meta-analyses [ 23 25 ]. Another topic – “perineural dexamethasone as an analgesic adjunct for peripheral nerve block” – has a definite possibility that this effect is mostly due to the systemic analgesic action of dexamethasone [ 28 , 29 ] described long ago.…”
Section: Resultsmentioning
confidence: 99%
“…TEA has been used throughout the perioperative period by administrating local anesthetic via epidural catheter. A number of studies have shown that the use of TEA in cardiac surgery attenuates the stress response, improves hemodynamic stability and shortens the postoperative ventilation/recovery time 8–17. However, the concern for epidural hematoma formation in the setting of high-dose intraoperative heparin administration has remained 18–20…”
Section: Discussionmentioning
confidence: 99%